PENGARUH KEGIATAN LITERASI PADA PENINGKATAN MINAT BACA SISWA SMA - Neng Lina Yulyana; Anita Yuliana; Woro Wuryani (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
The influence of literacy on increasing reading interest is the purpose of this study in order to find out the results of literacy activities carried out. This type of research is descriptive qualitative research. Sources of research data are teachers and students, as well as library officers and research data using data collection techniques, by means of interviews, observations, and questionnaires given to students. Analyzing data using interactive methods including data collection, data selection, data presentation, drawing conclusions and checking data. Based on the data that has been collected, described, and analyzed. The author can draw the conclusion that 1) the influence of literacy activities is able to make students have an interest in reading activities 2) the results of literacy activities seen from library visitors, the results of literacy programs, and questionnaire answers that show high school students know the meaning of literacy 3) there are obstacles in the program of literacy activities but can be handled easily.